Diseño de una herramienta para diagnosticar e interpretar el nivel de entropía en un sistema organizacional educativo (2020)
The term entropy hasits origins and basis in thermodynamics. However, it has been interpreted and implemented in different systems referring to social, cultural and ecological situations, among others. Its adaptation to different physical contexts has allowed to determine its value or a system's entropy level. One of the pioneers in implementing this term external to physics was Shannon (1948), who associated this concept with information theory and proposed a formula for calculating this indicator. From this, different authors have used entropy in the area of organizational systems, focusing entropy as an essential part of the study of information processes that have different variables with the internal and external environment. The level of entropy is also measured according to the diversity of information that exists in it, with the objective of making possible comparisons of organizations with themselves; from the evolution or transformation regarding their previous state or comparing the future scenarios associated to planned changes given by the objectives they want to develop. This comparison can be useful as a measure of effectiveness within the entities, taking into account the specific goals that each organization wants to achieve and if they are really achieving them with the current level of entropy. Although this indicator has been implemented and used for different organizational systems, there is not enough literature that conditions it to organizational educational systems. Therefore, this project develops a tool that allows the diagnosis and interpretation of the entropy level through a method that includes qualitative and quantitative information, considering that an educational organization is constantly changing and has different human, financial, material and intangible resources. According to this, the tool provides a variety of alternatives to the decision makers of the organization under study in order to help improving decision making and that they are in favor of the proposed goals. The application of this study was carried out in the Pontificia Universidad Javeriana Industrial Engineering Department, which is considered as an organizational educational system. The proposed tool is generic in itsform, but contextual in its approach, for each organization is unique and can be composed of different entities that change the structure. For its development, the starting point is to know the organization through its strategic planning, defining how it works and its goals. Afterwards, the necessary data is collected and debugged. For the characterization and proposal of solutions, engineering tools such as fishbone, statistical analysis, mathematical model, Pareto's frontier, and development of indicators were used, providing results that are analyzed based on the organization's information, considering its own characteristics such as its structure and available resources. Finally, a sensitivity analysis is carried out with the objective of determining the impact on the structure, the effect of external conditions and the impact on the organizational strategy; also, the designed tool is validated by experts which was accepted by the evaluators and desired for its implementation in other educational organizations. known as Six Sigma. This methodology addresses five phases: define, measure, analyze, improve and control (DMAIC), and it recommends the best practice for each of the phases of the DMAIC methodology used during the execution of a Six Sigma project. Following the above, in this project each of the phases will be presented and addressed in detail for the development of the tool explained above ensuring good practices and as a result a quality project that allows continuous improvement and provides a benefit to the case study organization. To carry out the study, primary and secondary information sources were used, which were cleaned and updated. Thirty-five percent of the data were collected, despite the contingency pf the pandemic and the backup of data from information sources. As a result of the application of the tool, the value of current entropy for each category with its respective classification is found. This provides a perspective of the current scenario to understand how the organization works; and thus, to obtain a range of solutions that take that state into account. Given this, multiple options are proposed to offer to the decision maker. This person should perform an analysis of each of them, considering that when a change is made, changes associated with the strategy, structure, processes, culture, etc. must be considered, which means having enough resources to perform any of them.